Spatial light modulator design and generation of structured electromagnetic waves using digital light processors - Yalcinkaya, F.; Koc, T.; Pala, Z. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2022)
Spatial light modulators (SLMs) are versatile devices used for optical studies. These instruments have a wide area of application in photonics. Additionally, SLMs have potential utility in different applications, such as biomedical applications, laser based surgery for precise cutting and as optical tweezers to separate cells in a petri container. However, the high cost of SLM devices prevents their widespread use in many areas, including industrial areas and scientific research laboratories. This paper demonstrates how to design a digital light processor (DLP) based low-cost SLM and describes how to obtain structured electromagnetic waves with the designed SLM. Therefore, this research was undertaken to design and produce a low-cost SLM device for optical applications. For this purpose, two prerequisites had to be fulfilled, the first was to use suitable components of a projection device with DLP-based digital micro-mirror device (DMD), and the second was to eliminate unnecessary SLM components from the system. Finally, holographic images reflected on the SLM screen were created by using Mathematica software program to change the amplitude and phase of the electromagnetic waves in order to obtain the structured electromagnetic waves.
Optica Applicata, Vol. 52, 2022, nr 3, s. 461-479
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; spatial light modulator; digital micro-mirror device; digital light processing; structured electromagnetic waves; orbital angular momentum; hologram